Transformasi Digital Transportasi: Peran Aplikasi TIJE dalam Meningkatkan Kualitas Pelayanan Publik di Jakarta - Agustina, Sabrina Khairina; Firman, Firman (Journal of Social Contemplativa, 2025)
Digital transformation demands that governments provide public services that are more effective, efficient, and transparent. One form of its implementation is the adoption of E-Government through the use of digital applications, such as TIJE (TransJakarta E-Ticketing) developed by PT Transportasi Jakarta. This application aims to facilitate public access to transportation services. However, in practice, its implementation still faces several challenges, including limited user understanding, an unfriendly user interface, and a lack of adequate public outreach from the service provider. This study is designed using a descriptive qualitative approach to examine how the TIJE application is implemented in public services and to identify the obstacles encountered in the field. Data collection techniques include in-depth interviews, participatory observation, documentation, and data triangulation, with data analysis based on the Miles and Huberman model. The study aims to provide a comprehensive understanding of system readiness, public response, and challenges in the application of digital technology to support E-Government in the transportation sector.